Endurance Diabetes Foot Exercise Based on Family Centered Care (EDFE-BFCC) to Reduce Blood Sugar Levels Patients Diabetes Mellitus Type 2 - Emmy Putri Wahyuni; Khalid Mustofa; Bertolomeus Seda; Tini Tini; Parellangi Parellangi (Health Notions, 2022)
Patients diabetes mellitus type 2 have the potential to suffer from various complications, both acute and chronic complications. The family in addition to providing support also has an important role in the process of preventing these complications. So the purpose of this study was to determine the effectiveness of endurance  diabetes foot exercise based on family centered care (EDFE-BFCC) in reducing blood sugar levels patients diabetes mellitus type 2 in the work area of Bengkuring Public Health Center, Samarinda. This study used a pre-experimental research design with a pre and post test research design without a control group. Researchers only intervened in one group without a comparison. The population in this study were all patients with Type 2 Diabetes Mellitus in the working area of Bengkuring Public Health Center, Samarinda. The sample used was 13 people by taking all members of the population according to the inclusion criteria. Diabetic foot exercise is modified with endurance movement, which is then through family empowerment to train family members with diabetes mellitus type 2. The effectiveness of the treatment was assessed by comparing the value of blood sugar levels during pre and post intervention. The results showed that p value = 0.001. Endurance diabetes foot exercise based on family centered care (EDFE-BFCC) is effective in lowering blood sugar levels during patients diabetes mellitus type 2.Keywords: diabetes foot exercise; endurance; family centered care; diabetes mellitus type 2